(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The objective of this article is to acknowledge the growing intersection between art, health and spirituality that many body artists carry out in their artistic-pedagogical projects, assessing how such experiences can impact the crisis of sensitivity the western body faces. To this end, some of the control and exploration mechanisms that neoliberal somatopolitics articulate are described, presenting the artist-educator as the appropriate figure to offer experiences capable of expressing and transforming the new compulsory ways of suffering. It concludes with a review of the possible meanings for the word cure (or healing), often used in these contexts.